Diabetes retinopathy is a poor predictor for renal and cardiovascular outcomes in comparison with hypertensive retinopathy in patients with chronic kidney disease. Issue 2 (August 2015) - Hwang, Hyeon Seok; Choi, Yoo A.; Kim, Se Young; Cho, Won-kyung; Nam, Yunju; Kim, Sung Jun; Yoon, Hye Eun; Chang, Yoon Kyung; Shin, Seok Joon; Yang, Chul Woo; Kim, Suk Young
Highlights Diabetic retinopathy was associated with rapid CKD progression. Diabetic retinopathy was associated with cardiovascular events and mortality in CKD. Hypertensive retinopathy was not associated with adverse outcomes.